Assessment of ecosystem services of oak forests, Tangir valley, district Diamer, Pakistan - Afzal, Muhammad; Ali, Anwar; Areeba-Binte-Imran; Ahmad, Naveed (Journal of Pure and Applied Agriculture, 2023)
Socio-cultural assessment is an extensively used method to quantify ecosystem services (ES). Present study investigated socio-economic importance of ES and measured carbon sequestration potential as regulatory ES in seven villages (Sheikhou, Jaglote, Glai, Adrkali, Shumari, Shabinal and Sobokot) of Tangir valley, district Diamer, Gilgit Baltistan. Questionnaires and interview based social survey was conducted to explore provisioning, regulatory, supporting and cultural ES. Further, forest attributes data was collected from 29 inventory plots in pure stand of Quercus ilex. Results showed that the provisioning services are comprised of fuel wood, fodder, grazing, food, leaf litter, fresh water and timber. In group discussion, community members gave top rank to the fodder (for their livestock) followed by fuel wood and litter collection. The highest correlation was shown between timber and monthly income (R2 = 0.42) whereas lowest was (R2 = 0.09) for NTFPs and fuel wood. Whereas negative correlation was perceived for agriculture, leaf litter, grazing, fodder and range land with R2 (0.31, 0.18, 0.17, 0.15 and 0.11), respectively. Local communities were less aware about regulatory and supporting services as these ES are taken as far-granted. Forest inventory showed that mean above ground biomass and carbon stocks were 72.46 and 34.06 t/ha, respectively. Similarly, total biomass and carbon stocks were 90.22 and 42.40 t/ha, respectively. Regarding cultural services, the area has great potential for eco-tourism due to outstanding landscape, scenic beauty and biodiversity. Present study suggests further indepth evaluation of ecosystem services provided by Quercus forests on the regional scales. © 2020 Department of Agricultural Sciences, AIOU